Community effects on women’s help-seeking behaviour for intimate partner violence in India: gender disparity, feminist theory, and empowerment - Hayes, Brittany E. (International journal of comparative and applied criminal justice, 2017)
While prior research has shown empowerment and gender disparity affect risk of intimate partner violence (IPV) in India, little research attention has been given to the effects of gender disparity and empowerment on the likelihood of help seeking for IPV. The present study used the nationally representative population-based 2005-2006 Indian National Family Health Surveys to assess individual/relationship- and community-level factors that influence help-seeking behaviour among a sample of women who reported having been involved in IPV. Results from the multilevel analyses revealed that working status, decision-making in the partner dyad, illiteracy, controlling behaviour, and severe physical or sexual abuse at the individual/relationship level affected the likelihood of help seeking. At the community level, age at marriage for women and the proportion of severe physical or sexual abuse affected help-seeking behaviours. Significant variation remains unexplained at the state level. Implications for programming are discussed.